2022
DOI: 10.3390/jcm11164657
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy in Pediatric Patients—Evaluation of Brain Structures’ Volume Using VolBrain Software

Abstract: Epilepsy is one of the most frequent serious brain disorders. Approximately 30,000 of the 150,000 children and adolescents who experience unprovoked seizures are diagnosed with epilepsy each year. Magnetic resonance imaging is the method of choice in diagnosing and monitoring patients with this condition. However, one very effective tool using MR images is volBrain software, which automatically generates information about the volume of brain structures. A total of 57 consecutive patients (study group) sufferin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In a large cross‐sectional study widespread patterns of altered subcortical volume and reduced GM thickness was observed in adults with epilepsy in comparison to healthy controls 13 . Data in children are more limited but overall, there are clear indications that epilepsy can result in brain volume loss 14 . In addition, our results might be limited by a selection bias, as visual assessment of volume loss has been shown to be unreliable.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In a large cross‐sectional study widespread patterns of altered subcortical volume and reduced GM thickness was observed in adults with epilepsy in comparison to healthy controls 13 . Data in children are more limited but overall, there are clear indications that epilepsy can result in brain volume loss 14 . In addition, our results might be limited by a selection bias, as visual assessment of volume loss has been shown to be unreliable.…”
Section: Discussionmentioning
confidence: 69%
“…13 Data in children are more limited but overall, there are clear indications that epilepsy can result in brain volume loss. 14 In addition, our results might be limited by a selection bias, as visual assessment of volume loss has been shown to be unreliable.…”
Section: Resultsmentioning
confidence: 89%
“…To today, the volumes of individual anatomical structures have been assessed via autopsy, computed tomography and MRI. In addition to studies using traditional measurement methods [40][41][42], more objective and practical automated analysis methods have also been developed [32,33,43]. It is well known that the thalamus mediates communication between sensory, motor, and cognitive brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, this is something different from supporting a systematic role of cerebellum in epileptogenesis, which was sporadically demonstrated in anecdotal cases with cerebellar masses [ 36 , 37 ]. Recent volumetric studies comparing epileptic subjects and healthy controls, indeed, showed volumetric anomalies in the brain, lateral ventricles, and putamen, but not in the cerebellum [ 38 ]. On these grounds, the role of the cerebellum and, in particular, CM1, in epilepsy remains undemonstrated.…”
Section: Discussionmentioning
confidence: 99%